Prevalence of Human Immunodeficiency Virus-1 Integrase Strand Transfer Inhibitor Resistance in British Columbia, Canada Between 2009 and 2016: A Longitudinal Analysis. (12th February 2019) - Kamelian, Kimia; Lepik, Katherine J; Chau, William; Yip, Benita; Zhang, Wendy W; Lima, Viviane Dias; Robbins, Marjorie A; Woods, Conan; Olmstead, Andrea; Joy, Jeffrey B; Barrios, Rolando; Harrigan, P Richard
Abstract: Background: Integrase strand transfer inhibitors (INSTIs) are highly efficacious and well tolerated antiretrovirals with fewer adverse side-effects relative to other classes of antiretrovirals. The use of INSTIs raltegravir, elvitegravir, and dolutegravir has increased dramatically over recent years. However, there is limited information about the evolution and prevalence of INSTI resistance mutations in clinical human immunodeficiency virus populations. Methods: Human immunodeficiency virus-1-positive individuals ≥19 years were included if they received ≥1 dispensed prescription of antiretroviral therapy (ART) in British Columbia between 2009 and 2016 (N = 9358). Physician-ordered drug resistance tests were analyzed and protease inhibitor (PI), reverse-transcriptase inhibitor (RT), and INSTI resistance were defined as having ≥1 sample with a combined, cumulative score ≥30 by Stanford HIV Drug Resistance Algorithm version 7.0.1. Results: Although most ART-treated individuals were tested for PI and RT resistance, INSTI resistance testing lagged behind the uptake of INSTIs among INSTI-treated individuals (11% in 2009; 34% in 2016). The prevalence of INSTI resistance was relatively low, but it increased from 1 to 7 per 1000 ART-treated individuals between 2009 and 2016 ( P < .0001, R 2 = 0.98). Integrase strand transfer inhibitor resistance mutations increased at integrase codons 66, 97, 140, 148, 155, and 263. Conclusions: The prevalence of INSTI resistance remains low compared with PI and RT resistance in ART-treated populations but is expanding with increased INSTI use.